Studies on Dibenzyltellurium(IV) Complexes with Some Schiff Base Ligands. - SRIVASTAVA, SHEKHAR; KUMAR SONI, DILIP; GAUTAM, DEEPA; SHANKAR GUPTA., HARI (Asian Journal of Chemistry, 2010)
Dibenzyltellurium(IV) complexes of tetradentate Schiff base ligands of the type (C6H5CH2)2 Te·SB (where SB = Schiff base ligand) have been synthesised and characterised by elemental analysis, conductivity, IR and PMR.